Billy Wilder on Assignment : Dispatches from Weimar Berlin and Interwar Vienna - Wilder, Billy, 1906-2002 (Book collections on Project MUSE., 2021)
"Before Billy Wilder (1906-2002) left Europe for the United States in 1934 and became a filmmaker, he worked as a newspaper reporter, first in Vienna and then in Weimar Berlin. This book, edited and introduced by Noah Isenberg and translated by Shelley Frisch, collects about 65 articles Wilder published in Austrian and German newspapers in the 1920s. The collection includes reported pieces on urban life, from a first-person account of Wilder's stint as a taxi dancer to an article about street sweepers; profiles of writers, movie stars and poker players; and dispatches from the international film scene, from reviews to interviews with such figures as Charlie Chaplin and Erich von Stroheim. Isenberg provides an introduction that gives biographical details and places the writings in context, emphasizing their historical moment and their connections to Wilder's later career"--